Odszkodowanie za szkodę planistyczną związaną z wejściem w życie uchwały krajobrazowej - Kamińska, Renata (Studia Prawa Publicznego, 2025)
The landscape resolution was introduced into the Polish legal order in order to effectively combat advertising chaos. However, due to inappropriate balancing out of public and private interest at the regulations preparation stage, from the very beginning of its existence the introduced tool is burdened with a defect that does not allow its effective use by municipal governments. This is because the legislator did not provide for a compensatory mechanism for damages resulting from the enforcement of the landscape resolution. In the assessment of the Constitutional Tribunal, this was a legislative omission which infringes upon constitutional standards for the protection of individual rights. Although preparations of an amendment to the provisions on landscape resolutions were initiated, which would allow compliance with constitutional requirements to be restored, the proposed changes do not adequately reflect the conclusions of the Constitutional Tribunal’s ruling nor the realities of the advertising market. The drafters have too directly adopted solutions based on existing mechanisms for compensating planning-related damages, without sufficiently considering the specific nature of the advertising resolution. The aim of this article is to present the issue of the mechanism for compensating the planning damage associated with the entry into force of a landscape resolution. First, it will outline the characteristics of landscape resolutions and the constitutional concerns regarding provisions that impose obligations on owners of advertising media forcing them to adapt them to new rules and conditions for their placement. It will then proceed to discuss the aforementioned draft amendments. Although its final form is currently unknown, an analysis of the draft’s assumptions will serve as the basis for presenting de lege ferenda postulates, the inclusion of which would allow the statutory regulation to be adjusted to constitutional standards.